2019
DOI: 10.3895/rbta.v13n1.7168
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização físico-química da polpa de bacaba e avaliação do comportamento reológico das suas suspensões

Abstract: A bacaba é uma palmeira tropical nativa da Amazônia e possui um alto potencial de exploração. Seus frutos são consumidos na forma de polpa, de cor creme-leitosa e de sabor agradável. A caracterização da polpa foi realizada segundo os parâmetros físico-químicos de pH, umidade, cinzas, fibra alimentar, proteínas, lipídeos, carboidratos totais e valor energético. O comportamento reológico das suspensões foi avaliado através de um viscosímetro rotacional na temperatura de 25ºC e os modelos reológicos de Ostwald-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…54 The high total fiber content found by researchers has also shown the potential of bacaba as a source of dietary fiber, 54,61 as the inclusion of these compounds in the daily diet is essential to maintain intestinal health and appears to be significantly associated with a lower risk of developing heart disease, stroke, hypertension, type 2 diabetes, obesity, and colon cancer. 62 Besides that, its high fiber content, found both in the edible part (∼21%) and in the almond (∼32%), 61 allows the material resulting from oil extraction to be incorporated into the production of products or food matrices. Based on the available evidence, the European Food Safety Authority Panel on Dietetic Products, Nutrition, and Allergies considers that a dietary fiber intake of 25 g per day is adequate for the correct intestinal function in adults.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…54 The high total fiber content found by researchers has also shown the potential of bacaba as a source of dietary fiber, 54,61 as the inclusion of these compounds in the daily diet is essential to maintain intestinal health and appears to be significantly associated with a lower risk of developing heart disease, stroke, hypertension, type 2 diabetes, obesity, and colon cancer. 62 Besides that, its high fiber content, found both in the edible part (∼21%) and in the almond (∼32%), 61 allows the material resulting from oil extraction to be incorporated into the production of products or food matrices. Based on the available evidence, the European Food Safety Authority Panel on Dietetic Products, Nutrition, and Allergies considers that a dietary fiber intake of 25 g per day is adequate for the correct intestinal function in adults.…”
Section: Reviewmentioning
confidence: 99%
“…Compiling the data published in the literature, most studies on bacaba have been carried out on its pulp (which represents about 32–45% of the fruit's total weight), and little work has been reported on its residues (mainly the almond) regarding the presence of bioactive compounds and their proximate composition. 18,54,58 Seixas et al , 59 Ribeiro et al , 61 Nascimento et al , 62 and Freitas et al 63 demonstrated that the edible part of bacaba (pulp plus peel) is hypercaloric (105–210 kcal per 100 g), slightly acidic (pH 5.70 and total titratable acidity of 0.12%), and has significant amounts of total soluble solids (2–12 °Brix), ashes (1.5–4.0%), proteins (3.5–7.0%), carbohydrates (4.5–16%), highlighting its high fiber (6.5–21.0%) and lipids (33.5–57.5%, dry weight) contents, which allows its inclusion in diets with a high energy value.…”
Section: Amazon Berriesmentioning
confidence: 99%